Consequences of Stroke on the Walking Parameters of Hemiparetic Patients in Borgou (Benin) - AZE, OSCAR DAGBEMABOU OLADOUNI; Adoukonou, Thierry; AKPLOGAN, BARNABÉ; Gbaguidi, Hermès; OJARDIAS, Etienne; Devillard, Xavier; Pascal, Giraux (My University, 2018)
Background: After a stroke, the accomplishment of daily life activities depends on the recovery of the motor function. Few data are available on post stroke walk recovery in the African context. This study aimed to determine the relationship between the age of stroke occurrence in Benin and its consequences on the walking speed and endurance of hemiplegic patients. Methods and findings: This was a cross-sectional pilot study and carried out at the University hospital of Borgou and included 22 hemiplegic people (63.8% men). The Measurement of Functional Ambulation Classification, Barthel Index and Modified Rankins Scale to evaluate the functional ability; and walking speed over 10 m and 6 minutes walking test (endurance), for the motor performance. The subjects (54.9 ± 5.5 years old) have an average speed of 0.82 ± 0.2 m.s-1 (16.7 ± 2.6 steps) and an average endurance of 329.3 ± 67.1 m. The comparison of the 2 sub-groups statistically different in age (p<0.05): G1: <55 years old (51 ± 3.2 years) and G2 ≥ 55 years old (58.8 ± 4.4 years) but no significant difference has seen in the walking speed, the number of steps and endurance (p>0.05). Conclusion: The young age of the participants did not allow making a remarkable difference between the walking performance, the number of steps and the endurance of the two subgroups of patients aged 43 to 68 years. Therefore we need the multicenter studies in order to study the real impact of age and other factors to the walking speed, endurance and performance.
Keywords: Stroke; Age; Walking; Performance; Benin